Determinants of access to credit by cocoa farmers in osun state, nigeria (International Journal of Agricultural Research, Innovation and Technology, 2020)
This study investigated the determinants of access to credit among cocoa farmers in Osun state, Nigeria. Specifically, the study described the socio-economic characteristics of cocoa farmers in the study area, examined the factors affecting access to credit by cocoa farmers in the study area; and identified the constraints faced by cocoa farmers in credit acquisition. The study was conducted in Osun state, south-western Nigeria. A multi-stage sampling procedure was used for selecting respondents for this study. A total number of 180 farmers were selected for the study. Data were analyzed using Descriptive statistics and logit Regression. The results for the entire respondents showed average values of 46 years for age, 25 years for year of experience, 8 persons for household size, and about 88% of the respondents have formal education. Farm size (p